2013
DOI: 10.1021/am4032289
|View full text |Cite
|
Sign up to set email alerts
|

N-Acyldithieno[3,2-b:2′,3′-d]pyrrole-Based Low-Band-Gap Conjugated Polymer Solar Cells with Amine-Modified [6,6]-Phenyl-C61-butyric Acid Ester Cathode Interlayers

Abstract: Efficient low-band-gap polymers are one key component for constructing tandem solar cells with other higher-band-gap materials to harvest wide absorption of the solar spectrum. The N-acyldithieno[3,2-b:2',3'-d]pyrrole (DTP) building block is used for making low-band-gap polymers. It is attractive because of its strong donating ability and relatively low highest-occupied-molecular-orbital level in comparison with the N-alkyl DTP building block. However, additional solubilizing groups on the accepting units are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 82 publications
0
15
0
Order By: Relevance
“…205,297 Duan et al 299 provide another option because they match the LUMO energy level of commonly used acceptor materials such as PCBM and ICBA, while they feature deep HOMO energy levels which endow them with good hole-blocking properties. Recently, many fullerene-based ESL materials have been developed by attaching polar groups such as phosphoric esters, 302 amines, 303 cationic ammonium, 304 and carboxylic acids 305 to fullerenes. Structures of the fullerene derivatives discussed in this section are summarized in Figure 44.…”
Section: Water/alcohol-soluble Polyelectrolytes As Eslsmentioning
confidence: 99%
“…205,297 Duan et al 299 provide another option because they match the LUMO energy level of commonly used acceptor materials such as PCBM and ICBA, while they feature deep HOMO energy levels which endow them with good hole-blocking properties. Recently, many fullerene-based ESL materials have been developed by attaching polar groups such as phosphoric esters, 302 amines, 303 cationic ammonium, 304 and carboxylic acids 305 to fullerenes. Structures of the fullerene derivatives discussed in this section are summarized in Figure 44.…”
Section: Water/alcohol-soluble Polyelectrolytes As Eslsmentioning
confidence: 99%
“…It was proposed that these hydrophilic organic interlayers can recover the lost open-circuit voltage (V oc ) and enhance the electron collection from the acceptor to ITO, because of the built-in field deriving from the interfacial dipole of the interlayer [11,34]. Under the guidance of this theory, several specific functional groups are introduced to alcohol-soluble interface materials, such as ethylene oxide [35], phosphonate [36,37], amino [38][39][40][41][42] and ammonium [43,44]. In our previous study, we have reported a series of alcohol-soluble small molecules including amino and ammonium derivatives, and used them as charge-injection materials for polymer lightemitting diodes (PLEDs) [45].…”
Section: Introductionmentioning
confidence: 99%
“…Although this pioneer study creates great potential in energy level engineering, these strategies still lack the attention of researchers. Chen's group reported organic solar cells based on N ‐acyldithieno[3,2‐b:2′,3′‐d]pyrrole having a low bandgap of 1.44 eV and a short circuit current density ( J sc ) of 17.1 mA cm −2 . More recently, Kesters et al .…”
Section: Introductionmentioning
confidence: 99%